Facilitators and Barriers to Implementing Standardized Outcome Measurement for Children With Cleft Lip and Palate. (January 2021) - Weidler, Erica M.; Britto, Maria T.; Sitzman, Thomas J.
Objective: Identify facilitators and barriers to implementing standardized outcome measurement in cleft care. Design: Cross-sectional, qualitative study. Setting/Participants: Participants included 24 providers and staff from a large, multidisciplinary cleft team in the southwest United States, 5 caregivers of children with cleft palate (with or without cleft lip) treated by this team, and 3 experts involved in implementing a cleft-specific standardized outcome measurement in the United Kingdom. Interventions: Semistructured, qualitative interviews were conducted exploring perceived facilitators and barriers to implementing standardized outcome measurement in cleft care. Interviews were audio-recorded, transcribed, and analyzed for content. The Consolidated Framework for Implementation Research was used to guide the interviews and analysis. The analysis focused on the characteristics of standardized outcome measurement that directly influence its adoption. Results: Participants identified both facilitators and barriers to implementing standardized outcome measurement. Facilitators included the strength and quality of evidence supporting improvements in cleft care delivery following implementation of standardized outcome measurement and the relative advantage of standardized outcome measurement over continuing the status quo. Barriers included the difficulty adapting standardized outcome measurement to meet local context and patient-specific needs and the complexity of implementing standardized outcome measurement. Conclusions: Providers, staff, and caregivers involved in cleft care perceive multiple benefits from standardized outcome measurement, while also recognizing substantial barriers to its implementation. Results from this study can be used to guide development of an implementation strategy for standardized outcome measurement that builds upon perceived strengths of the intervention and reduces perceived barriers.